PENGEMBANGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DAN MASYARAKAT BELAJAR UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN LIFE-SKILLS SISWA SEKOLAH DASAR - Winarni, Endang Widi (Pendidikan Dasar, 2009)
Abstract; The research purpose is to develop study model of science contextual through guided inquiry strategy in the level of II and to improve the concept understanding and life-skills for student at 5 degree in elementary school with the extended society learn. This research is a development research (Research and Development). Four study model science of contextual is developed cover: 1) guided inquiry strategy in the level II and extended society learn; 2) guided inquiry strategy in the level of II and limited society learn; 3) guided inquiry strategy in the level I and extended society learn; and 4) guided inquiry strategy in the level I and limited society learn. The validation result of study scenario and LKS by teacher and expert including into good criterion (suitable used with a bit revision). Observation result to the study scenario implementation was show that 80% of the activity step can be executed excellently. Student comments to model implementation that developed is student feels: 1) a challenge to do the activity 2) do not easy to give up in replying question; and 3) learn with pleasantness. The result of test-drive is shown that the completeness of learn student in classically experience equal to 28% and the student life-skills improvement equal to 17,66 %.